Validity and Reliability of the Sustainability Literacy Knowledge Domain among Pre-Service Science Teachers: A Rasch Analysis - Aldeva Ilhami; Topik Hidayat; Riandi; Siti sriyati (Faculty of Tarbiyah and Teacher Training UIN Jurai Siwo, Lampung, 2026)
Sustainability literacy is increasingly recognized as a critical competence for pre-service science teachers in addressing global sustainability challenges. The availability of psychometrically robust instruments in the Indonesian higher education context remains limited. This study aims to validate a sustainability literacy instrument within the cognitive domain using a Rasch dichotomous model to evaluate reliability, validity, item-fit statistics, and unidimensionality. The assessment instrument was designed to measure the extent of sustainability literacy among pre-service science teachers. A cross-sectional survey design was employed, involving 144 students from universities in Riau, Indonesia. Participants completed a sustainability literacy instrument comprising 30 multiple-choice items, developed based on the Sulitest framework. Data were analyzed using the Rasch measurement model with the assistance of Winsteps version 3.73 software, focusing on item fit indicators (Outfit MNSQ, ZSTD, and PTMEA Corr.), reliability indices, and principal component analysis of residuals. The results demonstrated that the instrument achieved good internal consistency (α = 0.85), high item reliability (0.94), and stable person reliability (0.84). Two items were identified as misfitting and recommended for revision, while the remaining items met acceptable MNSQ and PTMEA criteria. Furthermore, unidimensionality was confirmed, indicating that the instrument measures a single latent construct of cognitive sustainability literacy. The validated instrument can be used by teacher education institutions to diagnose pre-service teachers’ sustainability knowledge and to inform curriculum improvement. Its distinctive contribution lies in adapting an internationally recognized framework to the Indonesian higher education context through Rasch-based validation.